Componente comunicacional de una etapa del proyecto "adolescentes y jóvenes listos" adolescentes, jóvenes e incidencia para la prevención del VIH/SIDA en el marco de los derechos sexuales y reproductivos" - Chumpitaz Aguirre, Maria Sofia (2022)
Leading the communication component of a stage of the project "Adolescents,Youth and advocacy for HIV / AIDS Prevention in the framework of sexual and reproductive rights" was a very complete experience as it had various components ata professional and personal level that I was 100% involved, thus exceeding the expected results. The challenge assumed together with the adolescent and youth leaders, from Ventanilla and Carabayllo, trained in the exercise of their sexual and reproductive rights, especially in the prevention of HIV / AIDS, so that they would activate their peers in communication and visibility actions about the The importance of knowing your rights, as well as accessing differentiated health services, without discrimination or stigma, based on gender equality, interculturality and sexual diversity, was a journey that provided many satisfactions along the way and at the end of the process. It was a succession of training sessions, through workshops, conversations, and field work, using various communication resources in a strategic way, which allowed the involvement of adolescents and young people as a solid team despite their differences and empowered before the adult community and their peers in the streets and schools. It is important to remember that the project is carried out bearing in mind that in Peru, around 50% of AIDS cases are people under 31 years of age who were infected before the age of 21. Likewise, four births to mothers are registered every day under 15 years of age, that is, adolescent pregnancies (according to information published by Plan International). In addition, our country reports alarming figures of gender violence, 85% of the complaints made in the Women's Emergency Centers for family violence were made by women. The same occurs with violations of the rights of LGBT people, including harassment, violence and acts of discrimination, including homicides.